If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + -4r + 5 = 9r + 5 + -1r Reorder the terms: 5 + 7r + -4r = 9r + 5 + -1r Combine like terms: 7r + -4r = 3r 5 + 3r = 9r + 5 + -1r Reorder the terms: 5 + 3r = 5 + 9r + -1r Combine like terms: 9r + -1r = 8r 5 + 3r = 5 + 8r Add '-5' to each side of the equation. 5 + -5 + 3r = 5 + -5 + 8r Combine like terms: 5 + -5 = 0 0 + 3r = 5 + -5 + 8r 3r = 5 + -5 + 8r Combine like terms: 5 + -5 = 0 3r = 0 + 8r 3r = 8r Solving 3r = 8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-8r' to each side of the equation. 3r + -8r = 8r + -8r Combine like terms: 3r + -8r = -5r -5r = 8r + -8r Combine like terms: 8r + -8r = 0 -5r = 0 Divide each side by '-5'. r = 0 Simplifying r = 0
| 3x^2+18x+7=0 | | 0=(6-7x)10 | | (x-2)(y+3)=35 | | 2y+x=23 | | 5j-25=35 | | f(x)=x^4+x^3+x^2-9x-10 | | 8x-5=2x-5 | | 3-386+2= | | 4y+1y=13 | | x+1x+9=23 | | .38=2b+25*(-7) | | 17x^17=0 | | (Y-3)(Y^2+BY+C)=Y^3-27 | | 19(3-v)+10v=-15 | | -4(6x-7)-3(4+2x)= | | 3x+45=3(x-3) | | 6X(2x-1)= | | 3(2x-y)+6y= | | 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 | | -7+u=3 | | y-53=294 | | X^2+6x+6.75=0 | | 4x+7x-3=0 | | -101=w+5.3 |